Contextualisation of Reciprocal Alues in Fulfillment Aliqah as an Effort to Strengthen the Family - Firdawaty, Linda; Zuhraini, Zuhraini; Fajar, Mokhammad Samson (Institut Agama Islam Negeri Curup, 2024)
This study aims to explore the form of the absence of reciprocal or mutuality values that lead wives to file for a divorce, the factors causing the non-implementation of reciprocal values in financial support, and strategies for family strengthening. This research is a qualitative descriptive study based on the increasing trend of divorce cases filed by wives. Data was gathered from online news about the trend of divorce lawsuits triggered by either the wife's or husband's failure to apply reciprocal values. Interviews were conducted with maslahah family counselors, heads of religious affairs office, female scholars, academics, and judges of religious courts about the reasons wives file for divorce and efforts to strengthen families. Analysis was done qualitatively using the theories of mublà and social adaptation. The findings indicate that the absence of reciprocal values is triggered by gender-biased understanding dominating classical scholars' mindsets, which rely on patriarchal ethics and greatly favour men. This gender bias is implemented in Indonesian marriage regulations and becomes ingrained in the subconscious of society. The gender bias is implemented in Indonesian marriage regulation and becomes ingrained in the subconscious of humanity. Consequently, the obligation of financial support is seen as an absolute duty of the husband, without considering specific circumstances such as illness, disability or imprisonment, which may prevent the husband from fulfilling his obligations. On the other hand, when a husband cannot provide financial support, he is also unwilling to share domestic responsibilities, causing the wife to bear a double burden. As a result, conflicts and violence often occur. Therefore, there is a need to reinterpret the concept of financial support by following the messages of the Quran and the dynamics of modern society, implementing reciprocal values, and adapting roles. Socialising reciprocal values to all elements of society through relevant institutions and social media is essential for realising family strengthening.